MODEL CONTEXTUAL TEACHING AND LEARNING (CTL) UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS SISWA KELAS IV DALAM MATA PELAJARAN AQIDAH AKHLAK DI MI MUHAMMADIYAH PONOROGO - Diana, Nur; Cendriono, Nanang; Riyanto (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research is motivated by the low critical thinking ability of students in learning Aqidah Akhlak which is still dominated by lecture methods. This condition causes students to be less active in the learning process. The Contextual Teaching and Learning (CTL) model was chosen because it is able to connect the material with students' real lives so that learning becomes more meaningful. This study aims to describe the application of the Contextual Teaching and Learning (CTL) model and find out the results on the critical thinking skills of grade IV students at MI Muhammadiyah Ponorogo. The research uses a qualitative approach of the field research type. Data was collected through observation, interviews, and documentation. The results of the study show that the application of the Contextual Teaching and Learning (CTL) model is carried out through learning planning, the implementation of activities that relate the material to students' daily experiences, discussions, questions and answers, and reflections. The application of this model is able to improve students' critical thinking skills as seen from the courage to ask questions, express opinions, analyze problems, and draw conclusions. Learning becomes more active and fun. The conclusion of this study shows that the Contextual Teaching and Learning (CTL) model is effectively used to improve the critical thinking skills of grade IV students in the subject of Aqidah Akhlak at MI Muhammadiyah Ponorogo.